2013
DOI: 10.2174/1874325001307010109
|View full text |Cite
|
Sign up to set email alerts
|

Expressional Analysis of GFP-Tagged Cells in an In Vivo Mouse Model of Giant Cell Tumor of Bone

Abstract: Giant cell tumor of bone in a neoplastic stromal cell which survives for multiple passages in primary cell culture with a stable phenotype. In the pathological environment of GCT, the neoplastic nature of the mesenchymal stromal component drives local hematopoietic precursors to undergo fusion and form multinucleated osteoclast like giant cells. There is currently very limited knowledge about the pathogenesis of GCT due to the lack of suitable in vivo models for this tumor. Here we report stable gene transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Our results are consistent with previous studies in which GFP-labeled GCTB stromal cells were injected into the tibia of immunodeficient Balb/c nu/nu mice. 43 That study demonstrated the presence of green fluorescent, single stromal cells 1 year after injection. The latter scenario supports the notion and possibility that GCTB stromal cells survive in mice for a long time without forming large tumors.…”
Section: Discussionmentioning
confidence: 91%
“…Our results are consistent with previous studies in which GFP-labeled GCTB stromal cells were injected into the tibia of immunodeficient Balb/c nu/nu mice. 43 That study demonstrated the presence of green fluorescent, single stromal cells 1 year after injection. The latter scenario supports the notion and possibility that GCTB stromal cells survive in mice for a long time without forming large tumors.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, additional studies are required to evaluate the survival and tumorigenicity of the various cell types or combinations. Previously, it has been reported that GCTB stromal cells transfected with green fluorescence protein survived 52 weeks in vivo (24). However, isolation of stromal cells from GCTB in vitro results in the rapid loss of expression of receptor activator of nuclear factor-ÎşB ligand (44).…”
Section: Discussionmentioning
confidence: 99%
“…Although several in vivo GCTB models are available, studies on this tumor are restricted as the development of the in vivo model is incomplete, associated with a short survival time or does not induce osteolytic lesion (22)(23)(24). Stromal cells injected subcutaneously into immunocompromised mice do not produce giant cells (22,24,25). Furthermore, tumor tissues grown on chick chorioallantoic membranes do not appear to recruit chicken monocytes to synthesize new giant cells despite increased vascularization from the membrane, and the survival time is typically 10 days (23).…”
Section: Introductionmentioning
confidence: 99%
“…Although several in vivo GCTB models are available, studies on tumor therapeutics are hampered because in vivo development was either incomplete or had short survival time or did not induce osteolytic lesion. Stromal cells injected subcutaneously into immunocompromised mice do not produce giant cells (44)(45)(46). Moreover, tumor tissues grown on chick chorioallantoic membranes do not appear to recruit chicken monocytes to synthesize new giant cells and are unsuitable for drug administration, despite increased vascularization from the membrane, but only survive for 10 days (5,31).…”
Section: Discussionmentioning
confidence: 99%